A Good Perspective. Ethical and Religious Features of Tactics of Visuality in Józef Czapski’s Painting - Okupnik, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2015)
Being sensitive to human misery and suffering, Józef Czapski in many respects experienced a loss at various moments of his long life (1896-1993). Czapski was an individual painter who worked alone, keeping away from painters’ schools. He was interested in the problem of depicting other people’s pain. Czapski devised his own visual tactic, always associated with tact and “good perspective”. The artist avoided painting religious pictures and the two which he left behind are not his original visions but copies of the oeuvre created by others. The picture “D’apres Rouault” (1982) shows Christ Mocked. The second painting, “St. John the Baptist” (1997) was inspired by Fra Angelico. A characteristic feature of Czapski’s works is asceticism: moderate means of artistic expression, limited details and the focus on colour.